Prince of the people the life and times of a Brazilian free man of colour - Silva, Eduardo (Verso, 1993)
Prince of the People is an eloquent evocation of the daily life and culture of the slaves, freedmen and freedwomen, and free people of colour in nineteenth-century Brazil. Eduardo Silva provides a vivid case study of the life and ideas of the self-styled Dom Oba II d'Africa, a 'street character' who lived in Rio de Janeiro in the final decades both of slavery and of the Brazilian Empire. Through a rich historical investigation of the life, times and thinking of his subject the author makes a remarkable contribution to the cultural history of Afro-Americans in Brazil. To his social superiors Dom Oba II d'Africa was no more than a 'half-crazed' man whom the Brazilian Emperor, Dom Pedro II, was misguided enough to receive at the palace. To Rio's slaves and people of colour he was revered as Prince of the People. Many paid him tithe as if he were a true African sovereign; they went down on their knees at his solemn passage; they met in bars to read aloud the articles which he published both in the popular press and in the quality journals of the day. Eduardo Silva finds in this extraordinary figure a rare opportunity to explore popular mentalities in the period of the overthrow of slavery. What did slaves and free people of colour think about liberty, race relations, civic rights and duties at this time of great upheaval? Silva finds many vital clues in this fascinating reconstruction.
Keywords: Dom Obá <II, d'Africa>; Obá <II, d'Afrique>; Oba <d'Africa> -- II; Oba i I -- d'Africa -- ca. ?-1890; Geschichte 1800-1900; Affranchis - Brésil - Histoire - 19e siècle; Brésil - Relations interethniques; Dagelijks leven; Esclavage - Brésil - Histoire - 19e siècle; Negers; Noirs - Brésil - Moeurs et coutumes; Alltag; Alltag, Brauchtum; Geschichte; Schwarze; Sklaverei; Blacks -- Brazil -- Social life and customs; Freedmen -- Brazil -- Social life and customs; Slavery -- Brazil -- History -- 19th century; Brésil - 1822-1889; Brasilien; Brazil -- History -- Empire, 1822-1889; Brazil -- Race relations